2021
DOI: 10.3390/ma14226921
|View full text |Cite
|
Sign up to set email alerts
|

ROS-Based Nanoparticles for Atherosclerosis Treatment

Abstract: Atherosclerosis (AS), a chronic arterial disease, is the leading cause of death in western developed countries. Considering its long-term asymptomatic progression and serious complications, the early prevention and effective treatment of AS are particularly important. The unique characteristics of nanoparticles (NPs) make them attractive in novel therapeutic and diagnostic applications, providing new options for the treatment of AS. With the assistance of reactive oxygen species (ROS)-based NPs, drugs can reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 87 publications
(109 reference statements)
0
5
0
Order By: Relevance
“…[ 64 , 65 ] Nanoparticles based on reactive oxygen species are able to target atherosclerosis drugs to specific lesions, decreasing adverse reactions and prolonging therapeutic effects. [ 66 , 67 ] Macrophages are crucial factors in the progression of atherosclerosis. Employing indole molecule assemble with probucol to gain multifunctional nanoparticles, which are equipped with lots of excellent properties including preventing the differentiation of macrophages, eliminating the excessive production of reactive oxygen species, and reducing the level of inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…[ 64 , 65 ] Nanoparticles based on reactive oxygen species are able to target atherosclerosis drugs to specific lesions, decreasing adverse reactions and prolonging therapeutic effects. [ 66 , 67 ] Macrophages are crucial factors in the progression of atherosclerosis. Employing indole molecule assemble with probucol to gain multifunctional nanoparticles, which are equipped with lots of excellent properties including preventing the differentiation of macrophages, eliminating the excessive production of reactive oxygen species, and reducing the level of inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…They not only evade the mononuclear phagocyte system, thereby prolonging their circulation time in the bloodstream, but also exhibit effective targeting of lesions. NPs can be broadly classified into inorganic NPs and organic NPs [144,145].…”
Section: Ros Based Nanoparticlesmentioning
confidence: 99%
“…However, abnormally high ROS causes oxidative stress and disturbs the body's redox equilibrium, significantly impairing the structure and function of the intracellular macromolecule (80,81). Moreover, studies have shown that neurodegenerative diseases, cancers, diabetes, atherosclerosis, arthritis, and kidney diseases are all related to ROS accumulation (82)(83)(84)(85). Given the anti-oxidative and pro-oxidative activities of nano-enzymes and their unique advantages, constructing nano-enzyme-based therapeutic systems and applying them in biomedicine, such as anti-inflammatory, cancer, and especially cardiovascular diseases, are discussed in the article.…”
Section: Applicationmentioning
confidence: 99%